Acquisition of High‐Quality Spectral Flow Cytometry Data. Issue 1 (18th May 2020) - Fox, Amy; Dutt, Taru S.; Karger, Burton; Obregón‐Henao, Andrés; Anderson, G. Brooke; Henao‐Tamayo, Marcela
Abstract: Flow cytometry allows the visualization of physical, functional, and/or biological properties of cells including antigens, cytokines, size, and complexity. With increasingly large flow cytometry panels able to analyze up to 50 parameters, there is a need to standardize flow cytometry protocols to achieve high‐quality data that can be input into analysis algorithms. Without this clean data, algorithms may incorrectly categorize the cell populations present in the samples. In this protocol, we outline a comprehensive methodology to prepare samples for polychromatic flow cytometry. The use of multiple washing steps and rigorous controls creates high‐quality data with good separation between cell populations. Experimental data acquired using this protocol can be analyzed via computational algorithms that perform end‐to‐end analysis. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Preparation of single‐cell suspension for flow cytometry Support Protocol 1 : Lung preparation Support Protocol 2 : Counting cells on a flow cytometer Basic Protocol 2 : Surface and intracellular flow cytometry staining Support Protocol 3 : Single‐color bead controls